The Church as safe haven : Christian governance in China - Laamann, Lars Peter, (Studies in Christian Mission, 2018)
The Church as Safe Haven conceptualizes the rise of Chinese Christianity as a new civilizational paradigm that encouraged individuals and communities to construct a sacred order for empowerment in modern China. Once Christianity enrooted itself in Chinese society as an indigenous religion, local congregations acquired much autonomy which enabled new religious institutions to take charge of community governance. Our contributors draw on newly-released archival sources, as well as on fieldwork observations investigating what Christianity meant to Chinese believers, how native actors built their churches and faith-based associations within the pre-existing social networks, and how they appropriated Christian resources in response to the fast-changing world. This book reconstructs the narratives of ordinary Christians, and places everyday faith experience at the center. Contributors are: Christie Chui-Shan Chow, Lydia Gerber, Melissa Inouye, Diana Junio, David Jong Hyuk Kang, Lars Peter Laamann, Joseph Tse-Hei Lee, George Kam Wah Mak, John R. Stanley, R. G. Tiedemann, Man-Shun Yeung.